2017
DOI: 10.1161/jaha.117.006133
|View full text |Cite
|
Sign up to set email alerts
|

Recognized Obstructive Sleep Apnea is Associated With Improved In‐Hospital Outcomes After ST Elevation Myocardial Infarction

Abstract: BackgroundObstructive sleep apnea (OSA) is an independent risk factor for many cardiovascular conditions such as coronary artery disease, myocardial infarction, systemic hypertension, pulmonary hypertension, and stroke. However, the association of OSA with outcomes in patients hospitalized for ST‐elevation myocardial infarction remains controversial.Methods and ResultsWe used the nation‐wide inpatient sample between 2003 and 2011 to identify patients with a primary discharge diagnosis of ST‐elevation myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 25 publications
(40 reference statements)
10
35
0
Order By: Relevance
“…One study used the Berlin Questionnaire, which has a sensitivity and specificity of approximately 0.76 and 0.59 for mild and 0.77 and 0.44 for moderate OSA, respectively [50]. We observed a large discrepancy between the OSA prevalence reported using ICD-9-CM administrative coding (1.3%) compared to PSG [39]. The accuracy of ICD coding to identify patients with OSA has been criticized as suboptimal as it demonstrated poor sensitivity (58%) and specificity (38%) [51].…”
Section: Prevalence Of Osa Among Hospitalized Cvd Patientsmentioning
confidence: 70%
See 3 more Smart Citations
“…One study used the Berlin Questionnaire, which has a sensitivity and specificity of approximately 0.76 and 0.59 for mild and 0.77 and 0.44 for moderate OSA, respectively [50]. We observed a large discrepancy between the OSA prevalence reported using ICD-9-CM administrative coding (1.3%) compared to PSG [39]. The accuracy of ICD coding to identify patients with OSA has been criticized as suboptimal as it demonstrated poor sensitivity (58%) and specificity (38%) [51].…”
Section: Prevalence Of Osa Among Hospitalized Cvd Patientsmentioning
confidence: 70%
“…Three other studies reported the prevalence of OSA based on clinical parameters. Mohananey et al reported a much lower OSA prevalence of 1.3% using administrative data (International Classification of Diseases, Ninth Revision, Clinical Modification ICD-9-CM) [39]. Marin et al defined OSA as having met 3 criteria: heavy snoring, excessive daytime sleepiness, and having an ODI ≥ 10.…”
Section: Prevalence Of Osa Among Hospitalized Cardiac Inpatientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bearing these controversial data in mind, several studies have been performed to further elucidate the clinical relevance of OSA on the outcome of ACS patients. The findings of MOHANANEY et al [47] seem to support the theory of preconditioning of vessels in intermittent hypoxia. They identified a group of OSA patients with primary discharge diagnosis of STEMI from a nationwide sample.…”
Section: Prognostic Relevance Of Osa In Acs/amimentioning
confidence: 65%